The essence and features of corruption as an object of administrative and legal influence - E. O. Muzychuk (Bulletin of Kharkiv National University of Internal Affairs)
The article states that the formation of an understanding of the essence of corruption begins at the turn of the New Age, when the progressive thought of contemporary philosophers outlined the essence of legal behaviour, which was no longer influenced by religious dogmas.